Value stream mapping as lean healthcare's tool to see wastes and improvement points: the case of the emergency care of a university hospital - Cardoso, Wagner (Journal of Innovation and Healthcare Management, 2019)
Lean manufacturing emerged as an evolution to traditional production management systems amid the crisis that plagued Japan and then required Japanese companies to dry up their spending and optimize their costs. An initial tool for deploying lean manufacturing in any enterprise is value stream mapping. Based on the great importance and applicability of lean manufacturing with the help of mapping the flow of value in industrial environments, the question of research has arisen: can the application of value stream mapping in hospitals bring positive results as it has brought to the industries? Therefore, the main objective of this research is to analyze the productive environment of a university hospital, as a case study, identify bottlenecks and waste by current value stream mapping, and propose improvements with the aid of future value stream mapping. The expected results after the proposed improvements are implemented are reduction of the total lead time (time spent in the hospital), reduction of waste, better management in sight, and greater commitment of all those involved directly and indirectly in the process. This research, in its methodology, is classified as exploratory, qualitative, and used bibliographic review and case study to validate the content researched and potentiality of application in hospital environments.